2018
DOI: 10.1158/1055-9965.epi-18-0369
|View full text |Cite
|
Sign up to set email alerts
|

Tristetraprolin Is a Prognostic Biomarker for Poor Outcomes among Patients with Low-Grade Prostate Cancer

Abstract: We studied the utility of the tumor suppressor Tristetraprolin (TTP, ZFP36) as a clinically relevant biomarker of aggressive disease in prostate cancer patients after radical prostatectomy (RP). RNA expression was measured in an RP cohort of patients treated at Moffitt Cancer Center (MCC) and obtained from six publically available RP datasets with biochemical recurrence (BCR; total = 1,394) and/or metastatic outcome data (total = 1,222). TTP protein expression was measured by immunohistochemistry in a tissue m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…The physiological significance of TTP is highlighted by Zfp36 knockout mice, which develop severe inflammatory syndromes and growth retardation[114]. Moreover, TTP expression is frequently lost in human cancers, and this loss is often associated with poor clinical outcomes[115,116].…”
Section: Role Of Aubps In Crcmentioning
confidence: 99%
“…The physiological significance of TTP is highlighted by Zfp36 knockout mice, which develop severe inflammatory syndromes and growth retardation[114]. Moreover, TTP expression is frequently lost in human cancers, and this loss is often associated with poor clinical outcomes[115,116].…”
Section: Role Of Aubps In Crcmentioning
confidence: 99%
“…Additionally, the low time to reoccurrence in low-TTP tumors was more pronounced in low-grade tumors. This study suggested that TTP is a promising prostate cancer biomarker for predicting the low-grade radical prostatectomy prostate cancer patients that will have poor outcomes [66]. Another study similarly showed low TTP expression in prostate cancer compared to non-cancerous tissues [65].…”
Section: Ttp Family Proteins As Potential Biomarkersmentioning
confidence: 74%
“…Low TTP levels in prostate cancer shorten time to recurrence or metastasis compared with TTP-high tumors [66].…”
Section: Prostate Cancer Ttp/zfp36mentioning
confidence: 97%
See 1 more Smart Citation
“…Considering the relevance that bioinformatics has gained in translational medicine, several algorithms have been implemented in recent years for the identification of biomarkers with prognostic value in several types of cancer. As an example, gene expression profile analysis performed using genomic and clinical data stored in public repositories has led to the identification of biomarkers with potential prognostic value in prostate ( 36 ) and breast ( 37 ) cancer, among others.…”
Section: Discussionmentioning
confidence: 99%